2021
DOI: 10.1017/s0022215121001961
|View full text |Cite
|
Sign up to set email alerts
|

The effect of coronavirus disease 2019 on the hearing system

Abstract: Objective This study aimed to evaluate different auditory regions with audiological tests, based on the presumption that there may be damage to the structures in the hearing system after coronavirus disease 2019. Methods Twenty individuals with no history of coronavirus disease 2019 and 27 individuals diagnosed with coronavirus disease 2019 were compared. Pure tone, speech and extended high-frequency audiometry, acoustic immitansmetry, transient evoked and distortion product otoacoustic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 14 publications
1
16
0
2
Order By: Relevance
“…In a study evaluating ABR findings in individuals diagnosed with COVID-19, no significant difference was found compared to the control group although longer I, III, and V absolute latencies were obtained in this group. Nevertheless, III–V interpeak latencies were significantly longer in the test group than in the control group [17] . In our study, I, III, and V absolute latencies were significantly prolonged in the test group, but no significant difference was found between the I–III, III–V, and I-V interpeak latencies between the groups.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In a study evaluating ABR findings in individuals diagnosed with COVID-19, no significant difference was found compared to the control group although longer I, III, and V absolute latencies were obtained in this group. Nevertheless, III–V interpeak latencies were significantly longer in the test group than in the control group [17] . In our study, I, III, and V absolute latencies were significantly prolonged in the test group, but no significant difference was found between the I–III, III–V, and I-V interpeak latencies between the groups.…”
Section: Discussionmentioning
confidence: 64%
“…No significant difference was found in this study between the two groups in terms of TEOAE measurements, but the test group's values were lower at all frequencies [15] . In another study, low (0.125, 0.25, 0.5, and 1 kHz), high (2, 4, 6, and 8 kHz), and extended high frequency (10, 12.5, 14, and 16 kHz) pure-tone thresholds were significantly reduced in patients with COVID-19 history [17] . The 4 kHz TEOAE SNR rate was significantly lower in patients with COVID-19 history, and no significant difference was observed between control and test groups in other frequencies and the DPOAE test [17] .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In another study 12 , the authors investigated the effects of COVID-19 on the hearing system by administering PTA, speech audiometry, extended high-frequency audiometry, otoacoustic emissions (OAE) testing and auditory brainstem response (ABR) testing. This study enrolled 27 patients diagnosed with COVID-19 at least one month (mean 3.81 ± 2.11 months) earlier and treated at home and a control group of 20 individuals without history of COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Because there was no reason to assume that the virus would attack a specific ear and as previous studies have shown similar effects in both ears, 3 , 8 , 9 , 10 the results in the right and left ears of each participant were averaged. To answer our research questions, the air conduction thresholds were divided into three frequency ranges: low = 250–500 Hz, mid = 1000–3000 Hz, and high = 4000–8000 Hz.…”
Section: Methodsmentioning
confidence: 99%